Opening words from Dr. Arthur Chilingarov at NRF Open Assembly 2011 - Dr. Arthur, Chilingarov (Arctic Portal, 2011)
Dr. Arthur Chilingarov is Special Representative of the President of the Russian Federation for International Cooperation in the Arctic and Antarctic, Russian Academy of Sciences & Federal Assembly of the Russian Federation. Here he speaks at the 6th Northern Research Forum opening Session, held in Hveragerði, Iceland in September 2011. Please click on the link above to see the video.